Gender and Memory in the Work of Serbian-Jewish Writer Paulina Lebl Albala (1891–1967) - Koch, Magdalena (European journal of jewish studies, 2023)
The article focuses on how Serbian/Jewish hyphenated identity, gender, and memory intersect in the writing of Paulina Lebl Albala. It explores the dynamics of these factors in three texts: Dr. David Albala as a Jewish National Worker (New York: Leo Baeck Institute, 1943), Tako je nekad bilo [That’s How it Once Was] (Belgrade: Aleksandar Lebl, 2005); and Vidov život. Biografija dr. Davida Albale [Vid’s Life: A biography of dr David Albala] (Belgrade: Čigoja štampa, 2008). The article aims to examine two different approaches (‘masculine’ and ‘feminine’ discourses shaping, respectively, Jewish history and Serbian/feminist counter-history), two contrasting literary modes (biography and autobiography) and two disparate linguistic strategies (English and Serbian) used in the production of (counter)memory. The conclusion highlights that Lebl Albala employed two distinctive discourses in her writing: an official/public discourse with the male agent at its center, and an alternative/private discourse that pivots on the female subject.